Development of an item bank for food parenting practices based on published instruments and reports from Canadian and US parents. (1st August 2016) - O'Connor, Teresia M.; Pham, Truc; Watts, Allison W.; Tu, Andrew W.; Hughes, Sheryl O.; Beauchamp, Mark R.; Baranowski, Tom; Mâsse, Louise C.
Abstract: Research to understand how parents influence their children's dietary intake and eating behaviors has expanded in the past decades and a growing number of instruments are available to assess food parenting practices. Unfortunately, there is no consensus on how constructs should be defined or operationalized, making comparison of results across studies difficult. The aim of this study was to develop a food parenting practice item bank with items from published scales and supplement with parenting practices that parents report using. Items from published scales were identified from two published systematic reviews along with an additional systematic review conducted for this study. Parents (n = 135) with children 5–12 years old from the US and Canada, stratified to represent the demographic distribution of each country, were recruited to participate in an online semi-qualitative survey on food parenting. Published items and parent responses were coded using the same framework to reduce the number of items into representative concepts using a binning and winnowing process. The literature contributed 1392 items and parents contributed 1985 items, which were reduced to 262 different food parenting concepts (26% exclusive from literature, 12% exclusive from parents, and 62% represented in both). Food parenting practices related to 'Structure of Food Environment' and 'Behavioral and Educational' were emphasized more by parent responses, while practices related to 'Consistency of Feeding Environment' and 'Emotional Regulation' were more represented among published items. The resulting food parenting item bank should next be calibrated with item response modeling for scientists to use in the future.